2012
DOI: 10.4103/0973-6247.98924
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal thrombocytopenia and platelets transfusion

Abstract: Background:Neonates often develop thrombocytopenia at some time during hospital stay. Platelet transfusion are frequently given to them and are likely to result in unnecessary transfusion.Material and Methods:Thus, we analyzed thrombocytopenia in neonates, its prevalence, and relationship if any, between clinical condition and platelet transfusion in neonates, which would have been helpful in developing guidelines and/or protocols for platelet transfusion (and reducing the donor exposure) in neonates.Results:A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Thrombocytopenia affects up to 20-50% of all neonates admitted in neonatal intensive care unit [20]. In our study prevalence of thrombocytopenia was 38% which was similar to other studies [21,22]. Charoo BA [23] observed that 27% of babies with sepsis developed mild, 20% moderate and 12.5% developed severe thrombocytopenia.…”
Section: Discussionsupporting
confidence: 89%
“…Thrombocytopenia affects up to 20-50% of all neonates admitted in neonatal intensive care unit [20]. In our study prevalence of thrombocytopenia was 38% which was similar to other studies [21,22]. Charoo BA [23] observed that 27% of babies with sepsis developed mild, 20% moderate and 12.5% developed severe thrombocytopenia.…”
Section: Discussionsupporting
confidence: 89%
“…prevalence of thrombocytopenia among hospitalized neonates was between 22 -35% in other studies [32][33][34][35][36][37][38][39]. It was between 15-20% in studies by Khalessi N et al [7], Gupta et al [40], Anil K Gupta et al [22], Qazi Iqbala b et al [20]. However a higher prevalence of 69.9% was noted by Kyoung Hee Choi et al [41] & 53% by Zaccheaus A Jeremiah et al [5].…”
Section: Prevalence Of Culture Positivitymentioning
confidence: 94%
“…Decreased platelet count is particulraly due to hematologic disorders. [1][2][3] Other causes of thrombocytopenia include pre-eclampsia, HELLP syndrome and ITP. This disease affects 6% to 15% of all pregnant women usually at the end of pregnancy and is moderate.…”
Section: Introductionmentioning
confidence: 99%